Research Advance in Intestinal Mucosal Barrier and Pathogenesis of Crohn's Disease - Wang, Kuan (Gastroenterol Res Pract, 2016)
To date, the etiology and pathogenesis of Crohn's disease (CD) have not been fully elucidated. It is widely accepted that genetic, immune, and environment factors are closely related to the development of CD. As an important defensive line for human body against the environment, intestinal mucosa is able to protect the homeostasis of gut bacteria and alleviate the intestinal inflammatory and immune response. It is evident that the dysfunction of intestinal mucosa barriers plays a crucial role in CD initiation and development. Yet researches are insufficient on intestinal mucosal barrier's action in the prevention of CD onset. This article summarizes the research advances about the correlations between the disorders of intestinal mucosal barriers and CD.